Non-state Actors in China and Global Environmental Governance
XXII, 303 p. 24 illus., 5 illus. in color.
Keywords: "Non-state actors are playing increasingly important roles in enhancing China’s environmental governance and, more broadly, in modernizing China’s' governance system. However, systematic research on the subject has been astonishingly sparse. This timely volume, edited by internationally-renowned scholars, fills this gap and should lead to a growing interest in this critical issue." - Ye Qi, Cheung Kong Professor of Environmental Policy, School of Public Policy and Management, Tsinghua University "Focusing on the role of non-state actors, this book offers important insights regarding differences between the political and governing processes of China and the West. I know of no comparable approach to the topic of ecological modernization. The analytical framework applied systematically throughout the book should have a long shelf life." - Daniel Mazmanian, Chair of Presidential Working Group on Sustainability; Professor and former Dean, University of Southern California Sol Price School of Public Policy. This book is the first effort to develop a broad and deep perspective on the emerging space occupied by “non-state actors” in China in the context of global environmental governance. It will serve as a primer both for scholars seeking to understand China’s environmental governance system and for practitioners working with policymakers and administrators within that system. Individual chapters explore what works in achieving social change, domestically as well as globally, and will provide guidance to activists and directors of NGOs as well as scholars. .